A small Fish War: an example with frequency-dependent stage payoffs - Reinoud Joosten (Max Planck Institute for Research into Economic Systems, 2005)
Two agents possess the fishing rights to a lake. Each period they have two options, to catch without restraint, e.g., to use a fine-mazed net, or to catch with some restraint, e.g., to use a wide-mazed net. The use of a fine-mazed net always yields a higher immediate catch than the alternative. The present catches depend on the behavior of the agents in the past. The more often the agents have used the fine-mazed net in the past, the lower the present catches are independent from the type of nets being used. We determine feasible rewards and provide (subgame perfect) equilibria for the limiting average reward criterion using methods inspired by the repeated-games literature. Our analysis shows that a 'tragedy of the commons' can be averted, as sustainable Pareto-efficient outcomes can be supported by subgame perfect equilibria.
Keywords: C73; C72; Q22; Q20; 330; games with frequency-dependent stage payoffs; limiting average reward; equilibria; renewable common-pool resources; Allmenderessource; Erneuerbare Ressourcen; Nichtkooperatives Spiel; Dynamisches Spiel; Theorie